Hubungan Pola Asuh Orangtua Terhadap Kematangan Emosi Remaja - Basuni, Dita Nan Diya; Rahmawati; Khairun, Deasy Yunika (SISTEMA: Jurnal Pendidikan, 2021)
The purpose of this study was to determine the relationship between parental care and adolescent emotional maturity at SMP N 1 Serang City. The population is taken with the condition that adolescents aged 13-15 years from these criteria obtained the number of respondents 158 students through random sampling. The research method used is quantitative. The measuring instrument used is a questionnaire measuring scale consisting of aspects of parenting with a reliability value of 0.941 and a questionnaire measuring scale consisting of aspects of emotional maturity with a reliability value of 0.921. Based on the results of the regression test, the results obtained sig (2-tailed ) is 0.000 < 0.05, and the correlation coefficient (r) is 0.303 (p < 0.01). This means that there is a significant relationship between parenting and adolescent emotional maturity, where the higher the parenting style will have an impact on emotional maturity.